Patent landscape review on biodiesel production: Technology updates. (February 2020) - Mahlia, T.M.I.; Syazmi, Z.A.H.S.; Mofijur, M.; Abas, A.E. Pg; Bilad, M.R.; Ong, Hwai Chyuan; Silitonga, A.S.
Abstract: Biodiesel is a renewable fuel made from vegetable oils and animal fats. Compared with fossil fuels, it has the potential to alleviate environmental pressures and achieve sustainable development. In this paper, 1660 patents related to biodiesel production were reviewed. They were published between January 1999 and July 2018 and were retrieved from the Derwent Innovation patent database. The patents were grouped into five categories depending on whether they related to starting materials, pre-treatment methods, catalysts, reactors and processing methods, or testing methods. Their analysis shows that the availability of biodiesel starting materials depends on climate, geographical location, local soil conditions, and local agricultural practices. Starting materials constitute 75% of overall production costs and, therefore, it is crucial to select the best feedstock. Pre-treatment of feedstock can improve its suitability for processing and increase extraction effectiveness and oil yield. Catalysts can enhance the solubility of alcohol, leading to higher reaction rates, faster biodiesel production processes, and lower biodiesel production costs. Moreover, the apparatus and processes used strongly affect the oil yield and quality, and production cost. In order to be commercialized and marketed, biodiesel should pass either the American Society for Testing and Materials (ASTM) standards or European Standards (EN). Due to increases in environmental awareness, it is likely that the number of published patents on biodiesel production will remain stable or even increase. Highlights: Locally available starting materials have the potential to reduce production cost. Third-generation biodiesel are promising to overcome food and land issues. Transesterification process is an efficient technology to produce biodiesel. Selection of reactor is crucial to ensure quality and efficiency of biodiesel.